A Polygenic Risk Score as a Risk Factor for Medication‐Associated Fractures. (20th July 2020) - Manousaki, Despoina; Forgetta, Vincenzo; Keller‐Baruch, Julyan; Zhao, Kaiqiong; Greenwood, Celia MT; Mooser, Vincent; Bassett, JH Duncan; Leslie, William D; Richards, J Brent
ABSTRACT: Some commonly prescribed drugs are associated with increased risk of osteoporotic fractures. However, fracture risk stratification using skeletal measures is not often performed to identify those at risk before these medications are prescribed. We tested whether a genomically predicted skeletal measure, speed of sound (gSOS) from heel ultrasound, which was developed in 341, 449 individuals from UK Biobank and tested in a separate subset consisting of 80, 027 individuals, is an independent risk factor for fracture in users of fracture‐related drugs (FRDs). To do this, we first assessed 80, 014 UK Biobank participants (including 12, 678 FRD users) for incident major osteoporotic fracture (MOF, n = 1189) and incident hip fracture ( n = 209). Effects of gSOS on incident fracture were adjusted for baseline clinical fracture risk factors. We found that each standard deviation decrease in gSOS increased the adjusted odds of MOF by 42% (95% confidence interval [CI] 1.34–1.51, p < 2 × 10 −16 ) and of hip fracture by 31% (95% CI 1.15–1.50, p = 9 × 10 −5 ). gSOS below versus above the mean increased the adjusted odds of MOF by 79% (95% CI 1.58–2.01, p < 2 × 10 −16 ) and of hip fracture by 42% (95% CI 1.08–1.88, p = 1.3 × 10 −2 ). Among FRD users, each standard deviation decrease in gSOS increased the adjusted odds of MOF by 29% ( n MOF = 256, 95% CI 1.14–1.46, p = 7 × 10 −5 ) and of hip fracture by 30% ( n hip fracture = 68, 95% CI 1.02–1.65, p = 0.0335). FRD users with gSOS below versus above the mean had a 54% increased adjusted odds of MOF (95% 1.19–1.99, p = 8.95 × 10 −4 ) and a twofold increased adjusted odds of hip fracture (95% 1.19–3.31, p = 8.5 × 10 −3 ). We therefore showed that genomically predicted heel SOS is independently associated with incident fracture among FRD users. © 2020 American Society for Bone and Mineral Research.